Origin of Extremely Intense Southward Component of Magnetic Field (Bs) in ICMEs - Shen, Chenglong; Chi, Yutian; Xu, Mengjiao; Wang, Yuming (Frontiers in Physics, 2021)
The intensity of the southward component of the magnetic field (Bs) carried by Interplanetary Coronal Mass Ejections (ICMEs) is one of the most critical parameters in causing extreme space weather events, such as intense geomagnetic storms. In this work, we investigate three typical ICME events with extremely intense Bs in detail and present a statistical analysis of the origins of intense Bs in different types of ICMEs based on the ICME catalogue from 1995 to 2020. According to the in-situ characteristics, the ICME events with extremely high Bs are classified into three types: isolated ICMEs, multiple ICMEs, and shock-ICME interaction events with shocks inside ICMEs or shocks passing through ICMEs. By analyzing all ICME events with Bs ≥ 10nT and Bs ≥ 20nT, we find that 39.6% of Bs,mean ≥ 10nT events and 50% of Bs,mean ≥ 20nT events are associated with shock-ICME events. Approximately 35.7% of shock-ICME events have Bs,mean ≥ 10nT, which is much higher than the other two types (isoloted ICMEs: 7.2% and multiple ICMEs: 12.1%). Those results confirm that the ICMEs interaction events are more likely to carry extreme intense Bs and cause intense geomagntic storms. Only based on the in-situ observations at Earth, some interaction ICME events, such as shock-ICME interaction events with shocks passing through the preceding ICME or ICME cannibalism, could be classified as isolated ICME events. This may lead to an overestimate of the probability of ICME carrying extremely intense Bs. To further investigate such events, direct and multi-point observations of the CME propagation in the inner heliosphere from the Solar Ring Mission could be crucial in the future.